Understanding the conditions for passengers to consider accepting transfers between MyCiti and minibus taxi - Singh, Kapil (Department of Civil Engineering, 2026)
Cities across South Africa are constantly seeking to improve the level of public transport provision to better serve the users. Cape Town is seen as a leader in this respect; however, the existing public transport network is as fragmented as the rest of South Africa and generally offers a poor level of service in terms of safety, security, reliability, travel times etc. Cape Town's passenger rail system has been widely recognized as the backbone of the city's public transport network. Today, some lines are operating limited services and, due to headway constraints, the service has reached its current capacity limit on critical segments of the network. Said headway constraints are the direct result of a reduction in fleet, due to vandalism and poor maintenance, ageing rolling stock and a signaling system that it outdated. The steady decline of the rail service has resulted in thousands of passengers migrating to either minibus taxi or formal bus services, and some passengers not travelling at all. The introduction of the MyCiTi bus system was seen as a partial solution to the fragmented network as it was envisaged to replace the minibus taxi network as well as the Golden Arrow bus network by the year 2032 (CoCT, 2014). However, this approach has since been abandoned following the implementation and operation of MyCiTi Phase 1. Given the very low financial efficiencies realized with Phase 1 feeder services and expected for Phase 2A, the 2020 MyCiTi Business Plan for Phase 2A (CoCT, 2020) underlined the need to develop alternatives to the supply of feeder services for MyCiTi. As a result of the above, the MyCiTi Phase 2A System Plan was adapted to remove MyCiTi feeder services with the intention to explore mechanisms by which the existing MBT services can provide feeder services that complement MyCiTi Phase 2A operations. The City of Cape Town aims to integrate the public transportation network within the city through a number of initiatives. These initiatives include obtaining the authority to manage the Golden Arrow Bus Services contract and exploring the devolution of rail services but these are all long-term plans. In the short-term, the City is preparing to implement Phase 2A of MyCiTi offering services to connect Khayelitsha and Mitchells Plain to Wynberg and Claremont. MyCiTi will provide direct and trunk services whilst the feeder services to the MyCiTi trunk services will be provided by the MBT industry on an incentivized basis. This will require passengers to transfer between two modes with very different standards, operating characteristics, fare structures and levels etc. raising the question of will passengers make such a transfer? The research methodology for this study consisted of three steps. Firstly, a literature review was undertaken to better understand hybrid public transport systems, integrating public transport systems, v Understanding the conditions for passengers to consider accepting transfers between MyCiTi and Minibus Taxi transfers between modes and passenger transfer experiences, amongst other topics. Secondly, a small sample of passenger interviews were conducted in order to confirm that the attributes/conditions identified in the literature review process were valid and contextually relevant, and to identify possible attributes that may not have presented themselves in the literature review. Finally, a larger scale Best Worst Scaling (BWS) survey was undertaken where a sample on 232 respondents ranked the various attributes against each other in terms of the importance of the attributes. The BWS survey was administered using software that capture and analyzed the survey data. This research seeks to evaluate what public transport users value most when it comes to making transfers between modes in an effort to focus on improving these situations and removing some of these barriers altogether. The study found that the three most important attributes to the passenger, in order of preference, are Total Cost of the Journey or Cost, Threat of Criminal Behaviour or Safety and, Reliability in terms of scheduling or timetabling. The least important attributes have been identified as Protection from Weather, Retail Opportunities, Signage and Wayfinding and, Seating and Waiting Areas. Protection from Weather was the overall least important attribute. This study recommends that the City of Cape Town continue to pursue an integrated network as a priority, however, total integration is an expensive, long-term objective. The results of this study rank the attributes that are most important to passengers when considering transferring between modes and the City of Cape Town should therefore focus resources to address these areas starting with those most important to the public transport passenger.